Hyphenated techniques in liquid chromatography and their applications in forensic toxicology: A review - Sachil Kumar; Maciej J Bogusz (Wolters Kluwer Medknow Publications, 2021)
Conventional analytical methods, such as gas chromatography, high performance liquid chromatography (LC), ultra-violet, and others, are ineffective in addressing the increasing number of problems in forensic toxicology. Hyphenated analytical methods, wherein the separation method are coupled or combined with spectral methods, with the help of a proper interface, are the available alternative options. The key benefits of these methods are the requisites of low limits for detection, shorter analytical time, the possibility of automation, better reproducibility, and high precision and repeatability. This review discusses on some of the hyphenated analytical methods that involve LC as the separation tool, for their most recent applications in the area of forensic toxicology focusing on the screening of drugs of abuse, the usage of alternative matrices for monitoring drug abuse, analysis of chemical warfare agents, determination of doping agents and related substances, natural toxins, environmental poisons, and examination of food produce adulteration. The incorporation of the more user-friendly LC-interfaces, such as atmospheric pressure chemical ionization, and electrospray ionization in the LC- mass spectrometry has increased the popularity of this technique tremendously among scientists of different disciplines. Hyphenated approaches have extremely low constraints regarding the identification and quantification, and offer high reproducibility, with unparalleled potential.